2007
DOI: 10.1038/sj.onc.1210326
|View full text |Cite
|
Sign up to set email alerts
|

ZNF143 interacts with p73 and is involved in cisplatin resistance through the transcriptional regulation of DNA repair genes

Abstract: Zinc-finger protein 143 (ZNF143) is a human homolog of Xenopus transcriptional activator staf that is involved in selenocystyl tRNA transcription. We previously showed that ZNF143 expression is induced by treatment with DNA-damaging agents and that it preferentially binds to cisplatin-modified DNA. In this study, the potential function of ZNF143 was investigated. ZNF143 was overexpressed in cisplatin-resistant cells. ZNF143 knockdown in prostate cancer caused increased sensitivity for cisplatin, but not for ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(91 citation statements)
references
References 26 publications
3
88
0
Order By: Relevance
“…previously described (10,20). Briefly, 250 pmol of siRNA and 5 μL of lipofectamine mixture were combined with 3.0 × 10 5 PC3 cells in 500 μL of culture medium and incubated for 20 minutes at room temperature.…”
Section: Knockdown Analysis Using Small Interfering Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…previously described (10,20). Briefly, 250 pmol of siRNA and 5 μL of lipofectamine mixture were combined with 3.0 × 10 5 PC3 cells in 500 μL of culture medium and incubated for 20 minutes at room temperature.…”
Section: Knockdown Analysis Using Small Interfering Rnasmentioning
confidence: 99%
“…Whole-cell lysates were prepared as previously described (10,20). The indicated amounts of whole-cell lysates or nuclear extract were separated by SDS-PAGE and transferred to polyvinylidene difluoride microporous membranes (Millipore) using a semidry blotter.…”
Section: Western Blottingmentioning
confidence: 99%
“…Whole-cell lysates and nuclear extracts were prepared as described previously (Igarashi et al, 2007;Wakasugi et al, 2007). The indicated amounts of whole-cell lysates and nuclear extracts were separated by SDS-polyacrylamide gel electrophoresis (PAGE) and transferred to polyvinylidine difluoride microporous membranes (Millipore, Bedford, MA, USA) using a semidry blotter.…”
Section: Western Blotting Analysismentioning
confidence: 99%
“…Purification of GST-fusion proteins has been described previously (Igarashi et al, 2007;Wakasugi et al, 2007). GST-fusion proteins prepared as described above were bound to glutathione-sepharose 4B (GE Healthcare Bio-Science) in a 50% slurry in buffer X for 4 h at 4 1C, washed three times with buffer X and eluted with 50 mM Tris-HCl (pH 8.0) and 20 mM reduced glutathione according to the manufacturer's protocol (GE Healthcare Bio-Science).…”
Section: Purification Of Gst-fusion Proteinsmentioning
confidence: 99%
“…17 Interestingly, the DNp73g-mediated transactivation is altered by the polymorphisms TP53 PIN3 and PEX4 (codon 72/R72P), which affect the basal activity of the internal TP53 promoter as already described. 23 This suggests a cooperation between DNp73g and another transcription factor that is able to bind to the response elements encompassing those two SNPs, such as ZNF143, known to interact with p73 protein, 33 and for which several predicted binding sites are overlapping with PIN3. 34 For p63b, we observed that p53RE-A1/A2 is not essential, whereas the region 753-1042 is required to obtain the maximal p63b-mediated transactivation.…”
Section: Discussionmentioning
confidence: 99%